ANALISIS RENTABILITAS, FAKTOR-FAKTOR PRODUKSI USAHA PEMBUATAN TEMPE, DAN TATANIAGANYA DIKECAMATAN SUKARAJA - Nusril, Nusril; Nurung, M; Zuardi, Zuardi (Jurnal AGRISEP: Kajian Masalah Sosial Ekonomi Pertanian dan Agribisnis, 2004)
This study was aimed at analysis rentability factors influencing production, investigating marketing channel of tempe industry in District of Sukaraja. Samples were selected purposively, i.e. small medium and large tempe industry which is measured for its omset. For marketing channel analysis, puspose,.entrepreneu(retailer were taken while dealer, were selected using simple random sampling. Profit and gross margin ratio were used to analyze industry rentability while C-D and marketing margin were used for analyze second and third purpose. The research show that Tempe Industry in Sukaraja District were able to gain profIt. Furthermore, volume of soybean, labor, other input where significant influencing tempe production. For marketing channel were founded on research location with 72.52% of margin was a/located for producers.